Towards an explanatory model of mental health ethics by Northern Sotho traditional health practitioners of Capricorn District, Limpopo Province, South Africa - Moloantoa, Georgina Tukiso (My University, 2023)
Traditional health practitioners are the first to be contacted for mental illness in many parts of Africa. The literature shows that there are more traditional health practitioners (THPs) than western-trained mental health care practitioners in many African communities. Whilst there are calls for the recognition of traditional health practitioners, little is known about the processes that inform the traditional health practitioners’ ethical practices when dealing with patients with mental health issues. The aim of the study was to develop an explanatory ethical framework that informs traditional health practitioners in the management of mental health cases. Specifically, the objectives of the study were to: explore notions of mental health ethics as perceived by THPs; describe what THPs understand to be ethics in the management of mental health conditions; determine THP views regarding what is considered good ethical behaviour in the treatment of mental health conditions; and based on the THPs’ representations, develop an explanatory ethical framework informing THP’s management of mental health cases. Using the grounded theory approach, twenty traditional health practitioners were theoretically sampled for the study. The process of data collection and analysis was done simultaneously. Ten well-integrated concepts providing a thorough theoretical explanation of ethics informing the traditional health practitioner’s management of mental health cases emerged. The concepts included ethics, botho, ancestral guidance, consultations, admissions, referrals, treatment, remuneration, healing progress, and wrath of the ancestors. Five categories accounting for those concepts emerged from the study. An ethical framework informing the traditional health practitioner’s management of mental health cases is also presented. The study concludes by recommending that an ethical code of practice for THPs should be documented.
Thesis (Ph.D. (Psychology)) -- University of Limpopo, 2023
Keywords: Traditional health practitioners (THPs); Ethics; Mental health conditions; Psychiatric ethics; Mental health; Mental healing -- South Africa -- Limpopo; Healers